Compression and fatigue performance of additively manufactured NiTi architected shape memory alloys - Zwerink, B.B.; Biffi, C.A.; Fiocchi, J.; Mehrpouya, M. (IOP Publishing Ltd, 2025)
Additive manufacturing of architected materials—particularly lattice or porous structures—has gained significant attention in recent years due to their enhanced strength-to-weight ratios, load-bearing capabilities, and energy absorption properties. The integration of these structures with shape memory alloys offers multifunctional performance for advanced engineering applications. This study investigates the compressive fatigue behavior of NiTi lattice structures fabricated by Laser powder bed fusion. Initial quasi-static compression tests, carried out to full structural collapse, were used to define load levels for subsequent fatigue experiments. Fatigue testing was then conducted at 40 °C to induce pseudoelastic behavior, and an S–N curve was generated to characterize fatigue performance. Results showed that the NiTi lattice could sustain cyclic loading at 8 kN for an average of approximately 86 000 cycles, and around 18 000 cycles at 11 kN. Post-mortem microstructural analyses revealed martensite accumulation near fracture regions, attributed to stress-induced phase transformation.